Chemical and Phytomedicinal Investigations in Lunasia amara - G. Macabeo, Allan Patrick; Aguinaldo, Alicia M. (Pharmacognosy Reviews)
Since the ancient period up to the current time, plants have been utilized by man as medicinal agents on the basis of ethnomedical and folkloric beliefs. Later on, these speculations were transformed into a scientific basis as single drug agents. Basic sciences working on plants serving as brewing pot for pharmaceutical leads, use obtained natural products as new bioactive pharmaceutical prototypes. The battle on the search for phytomedicines that are safe and affordable to the reach of the common population is still on-going. Lunasia amara Blanco is a small green shrub found in rain forests of the Philippines, Eastern Java, Borneo, Sulawesi, Moluccas, Papua New Guinea and Australia, and a member of the alkaloid-bearing tribe of the Family Rutaceae. It is a medicinal shrub well-known for its beneficial effects in treating stomach pains, snake bites, hypertension, diarrhea and for enhancing sexual aggressiveness. Quinoline alkaloids and sesquiterpenes have been identified to occur in this plant. Activities related to CNS, antimicrobial property and cytotoxity have been associated with the quinoline alkaloids. This review aims to give an over-all picture regarding works that have been done on this medicinal plant as far as phytochemical and pharmacological aspects are concerned.
Keywords: Lunasia amara; quinoline alkaloids; sesquiterpenes; Rutaceae; CNS activity; antitubercular